Detection of Coxsackievirus A16 by reverse transcription loop-mediated isothermal amplification. (May 2012) - Yaqing, He; Wenping, Zong; Xionghu, Wang; Zhiyi, You; Shouyi, Yu; Hong, Yang; Yingchun, Dai; Guifang, Hu
Aims: A one-step, single-tube reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay was developed and validated for the detection of Coxsackievirus A16 (CA16).Methods & materials: An optimized RT-LAMP assay was tested for in its sensitivity, primers specificity, products specificity and reproducibility.Results: The detection limit of the RT-LAMP assay was 10 6 -fold dilution of stock virus or 81 copies in samples after RNA extraction, which was tenfold higher in sensitivity than the traditional reverse transcription PCR (RT-PCR) and equal to real-time RT-PCR. Digestion with a specific restriction enzyme EcoRI demonstrated that the amplified product was unique. The specificity of the assay was confirmed as it was demonstrated that the positive amplification only appeared among all CA16 stains, while no amplification was achieved in other viruses genetically related to hand, foot and mouth disease or similar clinical features. A good correlation between RT-LAMP and real-time RT-PCR was observed on the basis of the analysis of 33 clinical samples.Conclusion: RT-LAMP is a novel, alternative microbiological approach for rapid, sensitive and specific detection of CA16 in hand, foot and mouth disease.